Pengaruh Pembatasan Kapasitas Transportasi Umum Ganjil Genap Terhadap Mobilitas dan Dampaknya Pada Efektifitas PSBB - Nugroho, Aditya; Raga, Paulus; Parhusip, Veronica; Prahma, Kelvin Dianda Bella; Fadhil, Dimas Nu'man; Pratiwi, Sekar Widyastuti (Institut Transportasi dan Logistik Trisakti, 2022)
The purpose of the study was to determine the impact of restrictions on public transportation capacity and even odd exemptions to the effectiveness of Large-Scale Social Restrictions (PSBB) through mobility mediation. The respondents in this research was the society of DKI Jakarta, and the limits in this research is only seen from the society's point of view. The results of the discussion showed: restriction of public transportation capacity directly affects mobility, even odd exemption directly affects mobility, restriction of public transportation capacity directly affects the effectiveness of PSBB, even odd exemption directly affects the effectiveness of PSBB, mobility directly affects the effectiveness of PSBB, restriction of public transportation capacity has no direct effect on the effectiveness of PSBB through mediation mo bilitas, even odd exemption has an indirect effect on the effectiveness of PSBB through mobility mediation.